Innovations in First Nations health: exploring the effects of neoliberal settler colonialism on the Treaty Right to Health - Merrick, Rita (2020)
Graduate This thesis explores a recent innovation in First Nations health, the formation of Canada's First provincial-wide First Nations Health Authority (FNHA). Analyzing this service model against Indigenous assertions of a Treaty Right to Health expressed in the Numbered Treaties, I argue that the realizations of the Treaty Right to Health cannot solely be met under neoliberal models of increased Indigenous capacity in health care service administration. I assert that these models of devolution do not enable Treaty First Nations to achieve Indigenous self-determination in accordance with Treaty rights, relationships and responsibilities. The current discourse on First Nations health care only minimally accounts for the Treaty Right to Health, and where it does, it is devoid of Indigenous understandings of a Treaty Right to Health that encompasses access to healthy lands, waters, and livelihood for an achievement of holistic wellness. Mobilizing an Indigenous auto ethnographic approach which accounts for my own embodied positionally, this thesis problematizes the exclusion of holistic visions of health and well-being against settler governments' orientations toward a neoliberalized health care system. This thesis extends a comparative analytical lens to the political mobilizations of Indigenous advocacy bodies in the province of British Columbia, whose efforts under the New Relationship paradigm in Indigenous-state relations has resulted in an unprecedented practice of health care devolution.